Strengthening of shear-critical reinforced concrete T-beams with anchored and non-anchored GFRP fabrics applications. (October 2022) - A.H. AL-Shalif, Sadeq; Akın, Arife; Aksoylu, Ceyhun; Hakan Arslan, Musa
Abstract: In this study, the behavioral changes of reinforced concrete T -beams with insufficient shear strength under vertical loads as a result of strengthening with glass fiber reinforced polymer composites (GFRP) in various configurations was investigated comparatively. Nine reinforced concrete T -section shear-critical beams were produced. One of the beams is a reference and the other eight are wrapped with different GFRP methods. GFRP composites were applied along the shear spans of the beams in different wrapping styles, with or without anchorage. The effect of each GFRP application on the load-bearing, ductility and energy dissipation capacity of beams was investigated. As a result of the experiments, it was seen that shear failure was prevented by increasing the bonding surface between the GFRP and the concrete surface. In addition, it was observed that the anchored specimens strengthened with GFRP strips with a lower bonding surface were more effective in terms of ductility than all other non-anchor strengthening types. The shear capacity of beams having shear failure despite being strengthened was also compared with the approach of four different codes. It has been observed that the codes give different results from the experimental studies, especially due to the conservative acceptance of GFRP's deformation limits.